[Rezension von: Lofton, Kathryn, Consuming religion] - Chidester, David (Sociology of religion, 2018)
Going through the last few years of Sociology of Religion, I am struck by the disjuncture between the general run of articles and some of the books—the groundbreaking, game-changing books about religion—that are given attention through published reviews. My impression, perhaps posed too starkly here, is that there is a disconnection between these disruptive books and articles pursuing "normal" science in the sociology of religion, articles that feature solid research, empirically evidenced, leading to incremental advances in our approaches to leadership and adherence within religious institutions. Even articles dealing with dissatisfaction with any institutional religion, such as research on the "nonreligious," still operate within this institutional model for the sociological study of religion. After reading the articles in recent issues of Sociology of Religion, turning to the book reviews can induce shock, especially when some of the books challenge the entire enterprise of this normal science. To cite a few examples: Gordon Lynch, The Sacred in the Modern World: A Cultural Sociological Approach (2014; reviewed January 2015); Amy DeRogatis, Saving Sex: Sexuality and Salvation in American Evangelicalism (2015; reviewed June 2016); Roman R. Williams, ed., Seeing Religion: Toward a Visual Sociology of Religion (2015; reviewed March 2017); Saba Mahmood, Religious Difference in a Secular Age: A Minority Report (2015; reviewed September 2017). These books represent not contributions to a subfield or a subdiscipline but potentially revolutionary new perspectives on what counts as data for the sociology of religion.